2015
DOI: 10.3390/su7054997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Green Innovation on Environmental and Corporate Performance: A Stakeholder Perspective

Abstract: "Going green" has become an important environmental issue in contemporary business practice worldwide. This study examined the influence of a number of factors on green innovation and the consequences in terms of performance. The stakeholder theory was adopted to observe the effects of each stakeholder on the green innovation practices of companies and to determine how green innovation practices influence environmental and business performance. A research model with eight hypotheses was proposed to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
351
5
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(401 citation statements)
references
References 107 publications
33
351
5
12
Order By: Relevance
“…Visionary firm in adopting and implementing the green innovation will get positive response from stakeholders and eventually bring implications on the firm performance. The results of previous studies suggested that green innovations have in creased the cost savings and affected on the environmental performance and business performance (Lin et al 2013, Alhadid and As'ad 2014, Weng et al 2015. Based on the description above, the proposed hypothesis is:…”
Section: The Relation Of Green Innovation and Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Visionary firm in adopting and implementing the green innovation will get positive response from stakeholders and eventually bring implications on the firm performance. The results of previous studies suggested that green innovations have in creased the cost savings and affected on the environmental performance and business performance (Lin et al 2013, Alhadid and As'ad 2014, Weng et al 2015. Based on the description above, the proposed hypothesis is:…”
Section: The Relation Of Green Innovation and Firm Performancementioning
confidence: 99%
“…At this point, green innovation can enhance the value of prod ucts made by a firm, reduce the environmental costs, and eventually lead to a better firm performance. Alhadid and As'ad (2014), Chen et al (2006), andWeng et al (2015) ex plained that green innovation can improve the performance of firms that are pursuing CSR strategy. In this case, CSR needs to be directed to ethical issues of the environment as to reduce the negative impacts of company's activities, im prove profitability, financial gain, and competitiveness, and, at the same time, benefit the society (King and Lenox 2002, Klassen and Whybark 1999, Orlitzky et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The current study defines green innovation as new or modified products and processes, including technology, managerial, and organizational innovations, that help sustain the surrounding environment [36]. According to the theory of "decoupling", green growth means that while achieving economic development and social welfare improvement, resource consumption and environmental damage are reduced, really achieving the decoupling of economy, resources and environment.…”
Section: Green Innovation and Industrial Green Developmentmentioning
confidence: 99%
“…Firms should endeavor to improve their economic gains through value creation; through managing costs in their supply chain and adjust their strategies. According to Weng et al (2015), green innovation practices have a significant effect on firm performance (financial and non-financial). Firms should pursue activities that enhance not only efficiency and competitiveness but also leave a positive impact on the natural environment and the society (Carter & Rogers, 2008).…”
Section: Value Chain Performancementioning
confidence: 99%